The Evolutionary Relationship of Indian Skimmer Dragonflies (Odonata: Libellulidae): A Molecular Perspective - Hansra, Hardeep Singh; Walia, Gurinder Kaur; Dhillon, Gagandeep Kaur (Asian Journal of Biological and Life Sciences)
Background: This study addresses the challenging classification of the diverse Libellulidae (skimmer dragonflies) using molecular systematics. Materials and Methods: By analyzing the mitochondrial COI gene for 21 Indian species, including the first Indian sequences for Hylaeothemis apicalis and Onychothemis testacea and combining them with 84 public sequences, a robust 80-species dataset was assembled. Results: A clear DNA barcoding gap was confirmed, with low intraspecific (0.1-1.9%) versus high interspecific (2.5-24.1%) genetic divergence. Maximum Likelihood phylogenetic analysis resolved the family into six major clades and one distinct lineage. While the monophyly of genera like Sympetrum (Clade I) and Orthetrum (Clade II) was strongly supported, and some clades matched recent molecular studies, the recovered groups showed no correspondence with traditional, morphology-based subfamilies. This profound discordance was exemplified by the distant relationship between Diplacodes and Palpopleura. Conclusion: The study validates DNA barcoding for species identification in Indian libellulids, suggests potential cryptic diversity, and provides a phylogenetic framework necessitating a comprehensive taxonomic revision using integrative approaches.
Keywords: DNA barcoding; Molecular systematics; Odonata; Taxonomic revision.